Analysis of Completeness of Informed Consent Forms for Inpatients with Surgical Cases at the General Hospital Pku Muhammadiyah Bantul: Analisis Kelengkapan Formulir Informed Consent Pasien Rawat Inap Kasus Bedah Di Rumah Sakit Umum Pku Muhammadiyah Bantul - Setiyawan, Hery (Universitas Muhammadiyah Sidoarjo, 2025)
A hospital is a provider of health service facilities consisting of treatment and recovery as well as a health service facility consisting of outpatient services, inpatient services, emergency services and referral services. A medical record is a file that contains notes regarding the patient’s identity, examination, treatment, medical procedures and other services that have been provided to the patient. Medical recorders have the authority to carry out clinical classification systems and codefication of health-related diseases and medical procedures according to correct medical terminology. Medical terminology is a system used to organize a list of medical terms for diseases, symptoms and procedures. Disease terms or health conditions must be in accordance with the terms used in a disease classification system. Coding activities are assigning codes using letters and numbers or a combination of letters and numbers that represent data components. Activities carried out in coding include coding disease diagnosis and coding medical procedures. Incompleteness of informed consent forms or medical procedures includes a lack of understanding from doctors regarding the importance of filling out informed consent, resulting in negligence which creates obstacles in filling out informed consent which has a negative impact on doctors and the medical procedures given to patients. With this incompleteness, apart from having an impact on reducing the quality of medical records, it also has an impact on ensuring legal certainty for patients. The aim of the research is to determine the percentage of completeness, incompleteness, factors causing incompleteness, efforts to overcome incomplete informed consent for inpatient surgical cases at the PKU Muhammadiyah Bantul Hospital,Yogyakarta . Research method: using a qualitative descriptive method, with case studies, sampling using a purposive sampling method. Research results and conclusions with the percentage of complete informed consent 32.1%, incomplete doctor authentication 33.8%, incomplete patient witnesses 34.1%. The influencing factors are methods and man. Efforts to overcome incompleteness are through regularly scheduled outreach to nurses, doctors, medical records officers regarding the importance of completing the informed consent form. Check the list of informed consent data in the medical record file, whether it is complete or not.